ORGANISATION AND ALLOCATION OF TURNS AT THE OPUTA PANEL SESSIONS - Olayemi, Oluwakemi (Journal of Central and Eastern European African Studies, 2024)
This study investigates the turn-taking sequence, organisation of turns and the question patterns adopted during the examination of witnesses at the Oputa Panel sessions. The study employs purposive procedure in the selection of five questioning sessions as available on the YouTube. The data is transcribed and analysed using the linguistic approach of discourse analysis. In the findings, the counsel and the witness situate their talks firmly in the legal field with adherence to the turn-taking rules, explicit through yes/no responses, providing explanation to information seeking questions and also through the way the lawyers structure their questions to reveal narratives that shed light on the petition. The study notes that all activities and accomplishments at the Panel are carried out through the singular act of questioning. In order to prevent the language of conflict resolution procedures from seeming to alienate certain parties, particularly lay litigants, the study suggested the creation of a system for resolving disputes that is not closely tied to the usage of a particular linguistic form. Future efforts should focus on integrating additional language theories, such as psycholinguistics and critical discourse analysis.